Improvement of Learning Outcomes, Motivation, and Achievement of Students' Social Skills by Applying Student Teams Achievement Division Cooperative Learning Model through PhET Simulation Media - Wirdatul Jannah; Evendi Evendi; Safrida Safrida; Suhrawardi Ilyas; Muhammad Syukri (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to improve learning outcomes, motivation, and students' social skills by applying student teams' achievement division cooperative learning models through PhET simulation media. The method used in this study is quantitative. The research used is Quasi-Experimental. Instruments were used in the form of problems, questionnaires and, observation sheets. The results of the study data analysis prove that the average posttest of the experiment class obtained a score of 77.81, while the control class was 71.82, so that the results obtained in the experimental class were>75 or above from the KKM score that has been determined. Furthermore, the analysis of student motivation data proved an increase where the pretest score showed 60.5 and for the posttest results increased by a score of 66.56 and for the results of social skills learners showed an increase in each meeting in each indicator, which showed an excellent category. The conclusions in this study prove that the student teams achievement division cooperative learning model through PhET simulation media can improve learners' learning outcomes, motivation, and social skills